STOMATOPOD CRUSTACEA COLLECTED BY THE MISSION CORINDON II IN THE MAKASSAR STRAIT, INDONESIA - Moosa, Mohammad Kasim; Cleva, Regis (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1984)
Seventeen species of Stomatopoda belonging to five families have been collected in the Strait of Makassar, Indonesia during the Franco-Indonesian mission